Effects of Sublethal Organophosphate Toxicity and Anti-cholinergics on Electroencephalogram and Respiratory Mechanics in Mice - Bugay, Vladislav; Gregory, Summer Rain; Belanger-Coast, Matthieu Gibson; Zhao, Raymond; Brenner, Robert (Frontiers in Neuroscience, 2022)
Organophosphates are used in agriculture as insecticides but are potentially toxic to humans when exposed at high concentrations. The mechanism of toxicity is through antagonism of acetylcholinesterase, which secondarily causes excess activation of cholinergic receptors leading to seizures, tremors, respiratory depression, and other physiological consequences. Here we investigated two of the major pathophysiological effects, seizures and respiratory depression, using subcutaneous injection into mice of the organophosphate diisopropylfluorophosphate (DFP) at sublethal concentrations (2.1 mg/Kg) alone and co-injected with current therapeutics atropine (50 mg/Kg) or acetylcholinesterase reactivator HI6 (3 mg/Kg). We also tested a non-specific cholinergic antagonist dequalinium chloride (2 mg/Kg) as a novel treatment for organophosphate toxicity. EEG recordings revealed that DFP causes focal delta frequency (average 1.4 Hz) tonic spikes in the parietal region that occur transiently (lasting an average of 171  33 minutes) and a more sustained generalized theta frequency depression in both parietal and frontal electrode that did not recover the following 24 hours. DFP also caused behavioral tremors that partially recovered the following 24 hours. Using whole body plethysmography, DFP revealed acute respiratory depression, including reduced breathing rates and tidal volumes, that partially recover the following day. Among therapeutic treatments, dequalinium chloride had the most potent effect on all physiological parameters by reducing acute EEG abnormalities and promoting a full recovery after 24 hours from tremors and respiratory depression. Atropine and HI6 had distinct effects on EEGs. Co-treatment with atropine converted the acute 1.4 Hz tonic spikes to 3 Hz tonic spikes in the parietal electrode and promoted a partial recovery after 24 hours from theta frequency and respiratory depression. HI6 fully removed the parietal delta spike increase and promoted a full recovery in theta frequency and respiratory depression. In summary, while all anticholinergic treatments promoted survival and moderated symptoms of DFP toxicity, the non-selective anti-cholinergic dequalinium chloride had the most potent therapeutic effects in reducing EEG abnormalities, moderating tremors and reducing respiratory depression.